Analysis of the Dynamic Characteristic of Forklift Gearbox based on ADAMS - Wei Liangbao; Han Bin; Xu Liming; Zhao Shijia (Jixie chuandong)
Taking a CPC30 type forklift gearbox as the research object,first of all,the model is established by using the three dimensional modeling software SolidWorks. The dynamics simulation analysis under the condition of forward gearbox first gear is carried out in the ADAMS,the time domain and frequency domain diagrams of gear meshing force under the largest working condition of the engine are obtained. Through comparative analysis,the simulation values agreed with the theoretical value,the correctness of the dynamic model is verified. By using STEP function to simulate the engine for forklift gearbox drive,and using different loading times,the dynamic load of the engine under each loaded mode is got. The results of the research have certain guiding significance for the checking and optimization,vibration characteristics and stability of the forklift gearbox transmission system.